PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA TEMA 2 SUB TEMA 1 PEMBELAJARAN 3 DI KELAS IV SDI NAIMATA - Tolok, Christiana Ingi; Koroh, Taty R.; Nawa, Netty E. A. (Universitas Nusa Cendana, 2024)
This research was conducted at SD Inpres Naimata, Kupang City, with the aim of improving student learning outcomes regarding theme 2, sub-theme 1, learning 3 through the application of the STAD type cooperative learning model. The research method used is classroom action research. Data collection techniques are observation, test and documentation techniques. The data analysis technique is descriptive qualitative by looking for the percentage of data that has been collected and then clarifying it into a predetermined formula, with the research results showing that the data from observations of teacher activity in cycle I was with a value of 65.27 and cycle II with a value of 95.83%. , while the results of observations of student activities in cycle I with an average value of 66.59% and cycle II with an average value of 82.81%. In the first cycle of learning, there were 22 students who completed or met the specified KKM standards, namely 75, 8 students (36.36%) while 14 students (63.64%) did not complete. Furthermore, in cycle II, from 22 students, 22 students completed it (100%). Based on the research results, it was concluded that the STAD type cooperative learning model could improve student learning outcomes at SD Inpres Naimata, Kupang City.